Upaya peningkatkan minat dan hasil belajar vokal group dengan menerapkan metode permodelan pada siswa smp - Haryanto, Haryanto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this research is to increase the interest in learning and theresults of group vocal learning by using modeling methods in grade VIII B students of SMP N 1 Moga Pemalang. This research is a Class Action Research conducted through two cycles, each cycle consists of: planning, observation, action, and reflection. Data collection is done through documentation, observation, the use of questionnaires, and tests of learning results. Data analysis using quantitative descriptive and qualitative descriptive techniques. The results of group vocal learning activities can be concluded that group vocal learning with modeling methods has a positive impact in improving student learning outcomes characterized by improved student learning completion. Of the completed cycle 1 only 41% of students but in cycle 2 reached 89% of students. In addition, the application of modeling methods has a positive influence, which can increase students' learning interest indicated by the average student answers questionnaire results (questionnaires) that state that students are interested and interested in practicing group vocals with modeling methods. So the conclusion of this study is that modeling methods can positively affect the interest and learning of vocal groups in students at SMPN 1 Moga Pemalang.